Induction and Direct Resistance Heating Theory and Numerical Modeling - Lupi, Sergio; Forzan, Michele; Aliferov, Aleksandr (Springer International Publishing : Imprint: Springer, 2015)
This book offers broad, detailed coverage of theoretical developments in induction and direct resistance heating and presents new material on the solution of problems in the application of such heating. The physical basis of induction and conduction heating processes is explained, and electromagnetic phenomena in direct resistance and induction heating of flat workpieces and cylindrical bodies are examined in depth. The calculation of electrical and energetic characteristics of induction and conduction heating systems is then thoroughly reviewed. The final two chapters consider analytical solutions and numerical modeling of problems in the application of induction and direct resistance heating, providing industrial engineers with the knowledge needed in order to use numerical tools in the modern design of installations. Other engineers, scientists, and technologists will find the book to be an invaluable reference that will assist in the efficient utilization of electrical energy.